Studi Kesesuaian Kualitas Perairan untuk Budidaya Lobster Panulirus sp. pada Sistem Integrated Multi Tropic Aquaculture di Pemongkong, Lombok Timur - Ariana, Septian Dwi; Paryono; Amir, Sadikin (Jurnal Ilmu Kelautan Lesser Sunda, 2023)
Jukung Bay is a bay on Lombok Island. Lobster (Spiny lobster, Panulirus sp.) or crayfish is a type of crustacean that has important economic value. Water quality is very influential in lobster cultivation and plays a very important role in the survival of the lobster itself. Before cultivating lobsters, it is necessary to check the suitability of the water quality in the waters. Because water quality has a function that is greatly influenced by nature and human activities. Water quality is closely related to the process of mineral weathering in bedrock, the process of evapotranspiration in the atmosphere and the deposition of dust and salt by the wind as well as the activities of living creatures over time. This research was carried out in Ujung Betok Hamlet (Jukung Bay waters), Pemongkong Village, Jerowaru District, East Lombok Regency. The sampling locations were carried out at three points, namely, point 1 in IMTA KJA, point 2 in non-KJA waters and point 3 in non-IMTA KJA. At point 1, namely KJA, which is carried out using the IMTA system, at point 2, waters where there are no KJA and at point 3, KJA, people who cultivate lobsters do not use the IMTA system. The research was carried out from October 2022 to July 2023. In this time period, 3 samples were taken, namely in July 2022, October 2022 and February 2023. Based on the results of research using the IMTA system, it has not shown maximum results. This condition is due to the fact that at IMTA cultivation locations many floating net cage businesses are being carried out by local residents, so that the cultivation of the IMTA system being developed is still affected by the large number of cages owned by residents.